The issue of Arabic speaking skills among Malay learners: what is missing? - Che Haron, Sueraya (UIN MAULANA MALIK IBRAHIM MALANG, 2025)
The persistent challenges Malay learners face in acquiring Arabic speaking skills have been extensively studied for decades, yet practical solutions remain elusive. Previous research has approached this issue with the intent of solving it from various angles, including curriculum design, teaching methodologies, learning strategies, and extracurricular activities involving both educators and students, yet the problem persists essentially unchanged. This paper adopts a novel approach by examining the gaps in our efforts to address the issue. It seeks to identify where our strategies falter, what crucial elements are lacking, and where we should begin anew. Embracing the notion that returning to Arabic tradition may offer valuable insights, this study delves into Ibn Khaldun's concept of malakah, which emphasizes the practical and experiential dimensions of language mastery. This paper reevaluates prevailing pedagogical frameworks. The study highlights deficiencies in current approaches and proposes sensible, theory-driven solutions to enhance Arabic speaking proficiency among Malay learners